Perbandingan Manajemen Memori pada Sistem Operasi Windows dan Linux - Ariza, Rini; Reza Maulana, Muhammad; Rilvani, Elkin (International Forum of Researchers and Lecturers, 2025)
This research compares memory management between Windows 10 and Linux Ubuntu operating systems, focusing on the issues of memory fragmentation and memory leaks. Windows 10 applies paging and segmentation methods, which provide a high degree of flexibility, but on the other hand carry considerable system overhead. On the other hand, Linux Ubuntu uses the Buddies system which is more efficient in dealing with fragmentation issues. In handling memory leaks, Windows 10 relies on Garbage Collection, while Linux Ubuntu utilizes the Permchecker tool. This research provides knowledge related to the differences between Windows 10 and Linux Ubuntu operating systems in the context of handling memory management problems, especially on memory fragmentation and memory leak problems.